Avaliação de silagens de sorgo submetidas a diferentes níveis de inoculante bacteriano e períodos de estocagem - Jungbeck, Micaela (2021)
In order to evaluate the nutritional composition and fermentation parameters of sorghum silages subjected to different levels of bacterial inoculant (control, 7.5, 15, and 30 ml) and storage periods (20, 40 and 60 days), an experiment was conducted in the central region of Rio Grande do Sul. The research was conducted from January to July 2015, under a completely randomized experimental design in a 4x3 factorial arrangement (4 levels of inoculant and 3 storage periods), with 4 replications. Significant interactions were observed between storage periods x bacterial inoculant inclusion levels for RMS, acetic acid and NDFD. As for the storage periods, there were differences for pH, N-NH3, Ash, CP, NDF, Lignin, NFC, EE, TDN and milk production. Butyric acid and DM were influenced by storage periods and inoculant levels. The variables EP, GL, lactic acid, starch and ADF were not influenced by the treatments. RMS is approximately 99% when inoculated at a dose four times higher than recommended, except in silages stored for 60 days. The pH content was lower at 40 and 60 days, assuming that its decline occurred quickly, and that it helps to obtain the best RMS. The nutritional value and fermentation parameters of the silages did not dissipate difference between 40 and 60 days of storage. The treatments taken do not influence the losses due to the production of effluents and gases, as well as the levels of lactic acid, starch and the ADF fraction. Consider the DM, pH, acetic acid, butyric acid and N-NH3 values, as produced sorghum silages fit as well fermented. Indicating minimal losses, without significant loss in nutritional value, when preserved. An RMS was higher when a maximum dose of inoculant (30 ml) was used. Taking into account this variable to evaluate economically, the production obtains an economic return, through the reduction of losses and, in milk production.